2022
DOI: 10.1002/adma.202202625
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Nitric Oxide Depot for Hypoxic Tumor Vessel Normalization and Radiosensitization

Abstract: In cancer radiotherapy, the lack of fixed DNA damage by oxygen in hypoxic microenvironment of solid tumors often leads to severe radioresistance. Nitric oxide (NO) is a potent radiosensitizer that acts in two ways. It can directly react with the radical DNA thus fixing the damage. It also normalizes the abnormal tumor vessels, thereby increasing blood perfusion and oxygen supply. To achieve these functions, the dosage and duration of NO treatment need to be carefully controlled, otherwise it will lead to the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 55 publications
0
37
0
Order By: Relevance
“…Various strategies in drug delivery and formulation have been used to enhance the efficacy of synergistic drug combinations for the treatment of cancer–many of which employ polymer chemistry, biomaterial science, and nanoformulations for achieving optimum drug delivery. Of these approaches, polymeric nanoparticles are often formulated to coencapsulate and deliver therapeutic cargo for sustained delivery . For example, Houdaihed et al developed paclitaxel and everolimus-loaded polymeric nanoparticles grafted with PEGylated PLGA which increased systemic exposure and reduced neurotoxicity of the combination treatment in a breast cancer mouse model .…”
Section: Alternative Methods and Emerging Concepts In Combination The...mentioning
confidence: 99%
“…Various strategies in drug delivery and formulation have been used to enhance the efficacy of synergistic drug combinations for the treatment of cancer–many of which employ polymer chemistry, biomaterial science, and nanoformulations for achieving optimum drug delivery. Of these approaches, polymeric nanoparticles are often formulated to coencapsulate and deliver therapeutic cargo for sustained delivery . For example, Houdaihed et al developed paclitaxel and everolimus-loaded polymeric nanoparticles grafted with PEGylated PLGA which increased systemic exposure and reduced neurotoxicity of the combination treatment in a breast cancer mouse model .…”
Section: Alternative Methods and Emerging Concepts In Combination The...mentioning
confidence: 99%
“…Several studies reported that proper perfusion could efficiently alleviate hypoxia at the tumor site. 19 Thus, we explored the tumor oxygenation level after treatment with the different groups using the hypoxia-inducible factor (HIF-1α). As shown in Figure 5C, the Cu 2 O@Dex group showed that the HIF-1α level (green fluorescence) was significantly decreased compared with that in the PBS-treated group, and the semiquantitative analysis of fluorescence images in Figure 5D revealed that the hypoxia-positive area of the Cu 2 O@Dex group was 15.71%, while that of the PBS group was 63.67%, which implied that Cu 2 O@Dex could efficiently alleviate hypoxia by enhancing blood perfusion.…”
Section: Vasculature Normalization Ability Of Cu 2 O@dex Nps In Vivomentioning
confidence: 99%
“…According to the previous studies, NO, as an active gas molecule, can dilate vessels, increase blood perfusion, and promote endothelial cell coverage by pericytes for improving the structure of tumor vessels. 18,19,33 The tumor perfusion and the percentage of endothelial cell coverage by pericytes increase when the tumor vessels are normalized by NO. Therefore, we first studied if Cu 2 O@Dex could catalyze the GSNO generating NO through the 4-amino-5-methylamino-2′,7′-difluorescein-diacetate (DAF-FM DA) probe.…”
Section: Vasculature Normalization Ability Of Cu 2 O@dex Nps In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, increased intratumoral levels of nitrogen oxide (NO) and vascular endothelial growth factor (VEGF) through distinct mechanisms could effectively remodel tumor vasculature due to their potency in dilating blood vessels and in regulating angiogenesis, respectively [19,[25][26][27]. Tetramethylpyrazine (TMP), an alkylpyrazine isolated from traditional Chinese medicine, Ligusticum wallichii (Chuan Xiong), has been used for the treatment of varying vascular diseases in China for ~40 years, probably ascribing to its potency in promoting VEGF expression and NO production in vascular endothelial cells [28].…”
mentioning
confidence: 99%